The Quality of Carer–Patient Relationship Scale: Adaptation and Validation into Portuguese - Rosa Silva; Bobrowicz-Campos, E.; Paulo Santos-Costa; Isabel Gil; Hugo Neves; Apóstolo, João (International Journal of Environmental Research and Public Health, 2021)
Background: This study aimed to translate and adapt the Quality of the Carer–Patient Relationship (QCPR) scale into Portuguese and analyse both its psychometric properties and correlation with sociodemographic and clinical variables. Methods: Phase (1) Translate and culturally adapt the scale. Phase (2) Assess the scale’s confirmatory factorial analysis, internal consistency, construct validity, and correlations. Results: The experts classified the overall quality of the translation as adequate. A total of 53 dyads (cared-for person and carer) were assessed. In both versions, measures of central tendency and symmetry were also adequate, and the two factors under investigation had appropriate reliability, although in the conflict/critical factor, this was more fragile. Cronbach’s alpha values were 0.89 for the cared-for person version and 0.91 for the carer version. Conclusions: The QCPR scale showed satisfactory to good values of reliability. The assessment is essential to guarantee structured interventions by health professionals, since the quality of the dyads’ relationship seems to influence both older adults’ quality of life and carers’ health status. This study is a significant contribution to the introduction of the QCPR scale in the Portuguese clinical and scientific culture but also an opportunity to increase its use internationally.